Did the Bologna Process Challenge the German Apprenticeship System? Evidence from a Natural Experiment - Stephan L. Thomsen; Johannes Trunzer (Global Labor Organization (GLO), 2020)
Starting in 1999, the Bologna Process reformed the German five-year study system for a first degree into the three-year bachelor's (BA) system to harmonize study lengths in Europe and improve competitiveness. This reform unintentionally challenged the German apprenticeship system that offers three-year professional training for the majority of school leavers. Approximately 29% of new apprentices are university-eligible graduates from academic-track schools. We evaluate the effects of the Bologna reform on new highly educated apprentices using a generalized difference-in-differences design based on detailed administrative student and labor market data. Our estimates show that the average regional expansion in first-year BA students decreased the number of new highly educated apprentices by 3%-5%; average treatment effects on those indecisive at school graduation range between -18% and -29%. We reveal substantial gender and occupational heterogeneity: males in STEM apprenticeships experienced the strongest negative effects. The reform aggravated the skills shortage in the economy.
Keywords: I23; I28; J24; 330; Bologna Process; post-secondary education decisions; apprenticeships; higher education